(untitled) (Conjeturas Sociológicas, 2019)
El presente artículo tiene su enfoque desde la historia social y cultura del delito, pues a través del estudio de la administración de justicia, pone en el centro de su estudio un actor social poco considerado al momento de hacer historia social dado, quizá, sus dimensiones locales y la escasa disponibilidad de fuentes para estudiarlos: los comisarios de policía. Durante el siglo XIX mexicano esta clase de autoridades intermedias estaba lejos de considerarse un sector constituido por fieles representantes del Estado, cuando la mayoría de las veces eran actores que quedaban más arraigados a sus intereses personales que a las funciones que les confería el Estado. El artículo detalla algunas de las relaciones y conflictos cotidianos a lo que se enfrentaban los comisarios al ocupar de manera intermitente tal encargo. Intermediate authorities in Jalisco. The figure of the police commissioner in the rural environment during the 19th century This article has its approach from the social and cultural history of crime, because through the study of the administration of justice, it puts at the center of its study an underconsidered social actor when making social history given, perhaps, its local dimensions and the limited availability of sources to study them: police commissioners. During the 19th century Mexican, this class of intermediate authorities was far from being considered a sector made up of faithful representatives of the state, when most of the time they were actors who were more entrenched in their personal interests than functions conferred on them by the state. The article details some of the daily relationships and conflicts faced by the Commissioners to occupying intermittently their order.